Effect of handwashing on the reduction of Escherichia coli on children's hands in an urban slum Indonesia - Mahmud Aditya Rifqi; Umi Hamidah; Neni Sintawardani; Hidenori Harada; Sikopo Nyambe; Akira Sai; Taro Yamauchi (IWA Publishing, 2023)
Poor hand hygiene practice has been linked to an increase in the number of infections among children in urban slums. Hands are considered an intersection for bacterial transmission, but it is unclear whether the handwashing technique affects bacteria elimination. This study investigated the effect of handwashing on the concentration of Escherichia coli (E. coli) and factors related to its reduction among children in an urban slum in Bandung, Indonesia. We observed handwashing and conducted repeated hand swabs before and after handwashing among 137 participants. The mean E. coli concentration on the hands decreased after handwashing, with a higher reduction in E. coli count among students who used soap and had soap contact for more than 10 s during handwashing. Cleaning in-between fingers, using soap, soap contact for more than 10 s, and drying hands with a single-use towel were effective factors for reducing E. coli concentration after handwashing (p < 0.05). More than half of the swab samples (59%) tested positive for E. coli after handwashing, indicating that the children's handwashing technique was not effective in completely removing E. coli from the hands. Moreover, sustained and consistent handwashing practice as a daily behavior in children would maximize the effect. HIGHLIGHTS Fecal contamination was detected on the hands of students before and after handwashing.; The children's handwashing practice falls short of the standard, which affects the level of reduction of fecal contamination.; The short duration of soap contact with the hand (<10 s) is not enough to reduce the number of E. coli on the hands.; The results imply the need to focus on specific critical points in handwashing education.;